METHOD FOR EVALUATION QUALITY PARAMETERS OF TELECOMMUNICATIONS SERVICES - Zablotskyi, Valentyn; Selepyna, Yosyp; Lyshuk, Viktor; Yakymchuk, Natalia; Tkachuk, Anatolii (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
Currently, cellular networks have become widespread, the operators of which simultaneously use the infrastructure of the second-generation GSM networks, DCS to build third-generation W-CDMA networks that provide broadband multiple access with code division. At the same time, the problem of providing high-speed Internet connections is exacerbated due to the growing volume of data of diverse types transmitted over the Internet. When testing the entire network coverage area, the total number of voice calls increases, so a method of long-term measurement of the bit rate of information transmission via wireless communication channels is proposed, which does not increase the service information in the network. Mathematical modeling of Internet traffic consumption using the proposed measurement method is performed and entropy estimates of information channel bandwidth are given.